2011
DOI: 10.2174/187153011797881175
|View full text |Cite
|
Sign up to set email alerts
|

The Role of PPARβ/δ in the Management of Metabolic Syndrome and its Associated Cardiovascular Complications

Abstract: The association between metabolic syndrome and cardiovascular diseases raises important questions about the underlying pathological processes, especially for designing targeted therapeutic interventions. The Peroxisome Proliferators Activated Receptors (PPARs) are ligand-activated transcription factors that control lipid and glucose metabolism. Accumulating data suggest that PPARs may serve as potential targets for treating metabolic diseases and their cardiovascular complications. PPARs regulate gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 100 publications
(117 reference statements)
0
14
0
Order By: Relevance
“…In search of the mechanism(s) underlying the protective action of GW0742, we investigated whether PPAR- δ activation may affect the local inflammatory response associated with muscular metabolic injury. Although PPAR- δ has been implicated in the regulation of systemic inflammatory responses associated with metabolic dysregulation [7], so far, reports on anti-inflammatory effects of PPAR activation in skeletal muscle are rather scarce. Here, we show for the first time that in the skeletal muscle GW0742 reverts the diet-induced increase in the nuclear translocation of NF- κ B p65, a transcriptional factor that plays an important role in regulating the transcription of a number of genes, especially those involved in producing mediators of local and systemic inflammation (such as cytokines, chemokines, and cell adhesion molecules).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In search of the mechanism(s) underlying the protective action of GW0742, we investigated whether PPAR- δ activation may affect the local inflammatory response associated with muscular metabolic injury. Although PPAR- δ has been implicated in the regulation of systemic inflammatory responses associated with metabolic dysregulation [7], so far, reports on anti-inflammatory effects of PPAR activation in skeletal muscle are rather scarce. Here, we show for the first time that in the skeletal muscle GW0742 reverts the diet-induced increase in the nuclear translocation of NF- κ B p65, a transcriptional factor that plays an important role in regulating the transcription of a number of genes, especially those involved in producing mediators of local and systemic inflammation (such as cytokines, chemokines, and cell adhesion molecules).…”
Section: Discussionmentioning
confidence: 99%
“…PPAR isoforms display tissue-specific expression and gene-regulatory profiles. PPAR- δ , one of the most promising pharmacological target implicated in obesity-associated insulin resistance [7], is highly expressed in skeletal muscle, at 10- and 50-folds higher levels compared with PPAR- α and PPAR- γ , respectively [8]. However, its potential effects in affecting skeletal muscle glucose intake and insulin sensitivity are only now being elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…These studies should also carefully monitor the overall health of the experimental subjects since PPAR-b/d has several known positive effects on metabolic homeostasis and cardiovascular disease, and given its controversial role in carcinogenesis. 53,61 As a crude indicator of potential toxicity, we administered 20 nM GW0742 or GSK0660 via IVIT injection, to 7-day-old roomair rats, and assessed the retinal avascular area 3 days later. We found no difference between vehicle and the drug-injected groups, indicating that these drugs have no effect on the normal development of the retinal vasculature and no gross retinal vascular toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…However, in cell-based systems it is conceivable that a metabolite of the parent compound, not the parent compound itself, might be mediating the response through interactions with PPAR-γ. PPAR-δ activation improves the overall metabolic profile [10]. While no PPAR-δ agonists are yet approved for human use, they have been shown to enhance fatty acid oxidation in skeletal muscle, reduce serum triglycerides, increase serum high-density lipoprotein cholesterol and stimulate aspects of reverse cholesterol transport, improve glucose homeostasis, and trigger thermogenesis and weight loss [11].…”
Section: Introductionmentioning
confidence: 99%
“…Our study will investigate whether the protective and anti-inflammatory effects of PEA observed in a compression model of SCI are partially mediated by other PPAR isotypes, in addition to PPAR-α. In fact, while we have recently demonstrated that PPAR-α modulates the anti-inflammatory property of PEA in a mouse model of inflammatory pain [33], on the contrary Benetti and colleagues have shown that CB 1 , PPAR-γ and TRPV1 receptors mediated the antinociception induced by PEA in mice with chronic constriction injury of the sciatic nerve [10]. …”
Section: Introductionmentioning
confidence: 99%